The problem of the Federation Council in the Constitution of the Republic of Iraq in 2005... "An Analytical Study - Nasser kadhim Khalaf ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
The legislative authority is described in the Iraqi constitution of 2005 as being two-council, the Representatives Council and the Council of the Union, and the constitution specified the work of the Representatives Council in many of its items in detail, while it didn’t address the work of the Council of the Union except with a few items, so the Iraqi constitution gave all legislative powers to the Representatives Council while ignoring On the powers of the Council of the Union, even its establishment was entrusted to the Representatives Council, in a phenomenon unfamiliar with the constitutions and laws of countries that comply with the parliamentary system, and when the project of the Council of the Union was approved by the President of the Iraqi Republic at that time, those items related to it were not approved and didn’t active, but rather remained dead letter, and decided the active political forces in the Iraqi political scene to maintain the suspension of the Council of the Union and not activate it, as is the case with many laws and projects that remained without implementation because their application affects the strategy and plans of those forces.